EXPLORATION OF LEADERSHIP VALUE TRANMISSION IN A COLLEGE RECREATION ORGANIZATION - Cashion, Benjamin E (East Carolina University, 2021)
This was a mixed-methods study that explored the emergence, transmission, and reception of leadership values in an American southeast college recreation organization (CRO). A structured interview was conducted with the CRO director to determine his leadership values. Questions were designed to elicit specific values held by the director that were reflective of his leadership. Results from the in-depth interview elicited themes around the values of the director, methods of transmission of values of the director, skills the director had that he considered necessary to lead, and how the director governs his values in the work-environment. Based on the director's responses, a questionnaire was created and distributed to the CRO's frontline employees (FEs) to understand if the director exhibited these values and if these values were present in the work environment. The study occurred during the height of the COVID-19 pandemic when campus was largely closed. The FE questionnaire was electronically distributed to 220 employees. The response rate was low with 48 FEs attempting the questionnaire and 22 FEs completing questions related to the CRO director's values and method of value transmission; 23 FEs completed questions related to values present in the CRO and method of value transmission from direct supervisors. While descriptive, the results from the FE questionnaire identified four tiers of value congruence between the director and CRO. There was also a difference in the methods of transmission with FE supervisors rated higher than the director on communication via actions, language, and written communication.
Keywords: Recreation leadership; Recreation--Management; College students--Recreation; Educational leadership